Class I malocclusion with severe double rotrusion treated with first premolars extraction - Ricardo Moresca (Dental Press Editora, 2014)
Angle Class I malocclusion with bimaxillary protrusion is characterized by severe buccal tipping of incisors, which causes upper and lower lip protrusion. First premolars extraction is recommended to reduce facial convexity as a result of anterior teeth retraction, which keeps canines and first molars in key to occlusion. In order to yield orthodontic results that are compatible with ideal esthetic and cephalometric outcomes, the space closure phase needs to be carried out with overbite and incisors torque control. The majority of cases also requires maximum anchorage of posterior teeth. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as a requirement for the title of certified by the BBO.